Expression of orphan nuclear receptor NR4A2 in gastric cancer cells confers chemoresistance and predicts an unfavorable postoperative survival of gastric cancer patients with chemotherapy. Issue 19 (2nd July 2013) - Han, Yifang; Cai, Hui; Ma, Liye; Ding, Yibo; Tan, Xiaojie; Chang, Wenjun; Guan, Wei; Liu, Yan; Shen, Qiuxia; Yu, Yongwei; Zhang, Hongwei; Cao, Guangwen
<x xml:space="preserve">Abstract</x> BACKGROUND NR4A2, an orphan nuclear receptor essential in the generation of dopaminergic neurons, has been recently linked to inflammation and cancer. This study sought to identify the role of NR4A2 on chemoresistance and postoperative prognosis of gastric cancer (GC). METHODS NR4A2 was transfected into GC cells to investigate its effects on chemoresistance to 5‐fluorouracil and the tumorigenicity in nude mice. This study also investigated prostaglandin E2 (PGE2)‐induced NR4A2 expression and its effect on chemoresistance. Surgical specimens from patients with stage I through III GC were examined immunohistochemically for NR4A2 expression. Median follow‐up time was 76 months for 245 patients. RESULTS Ectopic expression of NR4A2 significantly increased the chemoresistance and attenuated 5‐fluorouracil–induced apoptosis. Transient treatment of GC cells with PGE2 significantly upregulated NR4A2 expression via the protein kinase A pathway and increased the chemoresistance. Ectopic expression of NR4A2 significantly increased the tumorigenicity. In clinical samples, NR4A2 was preferentially expressed in lymphocytes and epithelial cytoplasm in adjacent mucosa. High expression of NR4A2 (immunoreactive score ≥ 3) in cancer cells significantly predicted an unfavorable postoperative disease‐specific survival of patients with stage I to III GC (P = .011), especially for those who received 5‐fluorouracil–based chemotherapy (P = .016). This effect was not found in those without the chemotherapy. In multivariate Cox analyses, age, TNM (tumor/node/metastasis) stage, and high NR4A2 expression significantly predicted an unfavorable postoperative survival. CONCLUSIONS High NR4A2 expression in GC cells confers chemoresistance, attenuates 5‐fluorouracil–induced apoptosis, and predicts an unfavorable survival, especially for those who received chemotherapy. NR4A2 might serve as a prognostic and predictive factor and therapeutic target for patients with GC. Cancer 2013;119:3436–3445.. © 2013 American Cancer Society.